Venous thrombosis and hormonal contraception: what's new with estradiol-based hormonal contraceptives? - Fruzzetti F; Cagnacci A (Dove Medical Press, 2018)
Franca Fruzzetti,1 Angelo Cagnacci2 1Department of Obstetrics and Gynaecology, Santa Chiara Hospital, University of Pisa, Pisa, Italy; 2Institute of Obstetrics and Gynecology, Department of Medical Area, University of Udine, Udine, Italy Objective: Estradiol (E2)-based hormonal contraceptives impact less than ethinylstradiol (EE) contraceptives on venous thromboembolism (VTE) in comparison to formulations with EE.Study design: In this article, the pharamacologic data of EE and E2 were briefly reviewed, along with the induced biologic effect. These data were then related to a recent large international prospective, controlled, non-interventional cohort active surveillance study, on the cardiovascular risk of users of different types of combined estro-progestin contraceptive (CEPC).Results: The crude HR for E2-valerate (E2V)/dienogest vs other CEPCs with EE was 0.8 (95% CI, 0.4–1.6), but when the data were corrected for age, body mass index, duration of use, and family history of VTE, the corresponding adjusted HR was 0.5 (95% CI, 0.2–1.0). A comparison of the E2V/dienogest and EE/levonorgestrel groups showed that the two contraceptives induced a similar VTE risk with the crude and adjusted VTE HRs of 0.7 (95% CI, 0.3–1.8) and 0.5 (95% CI, 0.2–1.3), respectively. Similar results were obtained when the observation was prolonged to January 2017.Conclusions: The reduced impact of E2 vs EE on coagulation translates into the epidemiologic evidence of a reduced number of events in E2V vs EE users, when progestins other than levonorgestrel are used. However, E2 may continue to negatively impact on the risk of VTE, and this should not be forgotten at the time of prescription. Family history of VTE or thrombophilia, age, and obesity are risk factors for VTE too. If these risk factors are not taken into consideration and excluded, they can overcome or hide the higher safety of E2 vs CEPCs with EE. Keywords: estradiol, estradiol valerate, contraception, venous thromboembolism, dienogest